Работа над конструкциями на практических занятиях по русскому языку со студентами—нефилологами - Саакян, Р. Н.
The author of the article touches upon the work on scientific style in the national audience on the advanced level of teaching. She investigates the grammatical structure of several constructions, the ways of making their usage more active in the speech of the students non —philologists. The perfection of speech skills and abilities of the students is seen on the concrete material — on the professional syntactical whole. The main conclusion of the article is the following: the work on the constructions in question not only promotes the improvement of the culture of Russian speech, enriches the professional lexis, but also develops abstract thought of the students.
Keywords: Методика преподавания русского языка